Pet ownership and survival in the elderly hypertensive population - Chowdhury, E.; Nelson, M.; Jennings, G.; Wing, L.; Reid, Christopher (Lippincott Williams & Wilkins, 2016)
Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved. OBJECTIVES:: To assess the association of pet ownership and all-cause and cardiovascular mortality over a long-term follow-up among elderly treated hypertensive participants. METHODS:: Pet-ownership data from a subcohort of the Second Australian National Blood Pressure study were used. Participants were aged 65–84 years at enrolment (1995–1997) and responded to a pet-ownership questionnaire during year 2000. Participants’ survival information was determined over a median of 10.9 years that includes Second Australian National Blood Pressure in-trial period (median 4.2 years) together with posttrial follow-up period (median 6.9 years). For the current study, end points were any fatal cardiovascular event and all-cause fatal events. RESULTS:: Of those who responded to a pet-ownership questionnaire (4039/6018 – 67%), 86% (3490/4039) owned at least one pet at any-time during their life (current or previous pet owner), with 36% (1456/4039) owning at least one pet at the time of the survey. During the follow-up period, 958 participants died including 499 deaths of cardiovascular origin. Using a Cox proportional hazard regression model adjusting for possible confounders, there was a 22 and 26% reduction in cardiovascular mortality observed among previous and current pet owners, respectively, compared with those who had never owned one. A similar nonsignificant trend was observed for all-cause mortality once adjusted for potential confounders. CONCLUSION:: Pet ownership was associated with an improved cardiovascular disease survival in a treated elderly hypertensive population.